Measuring the growth of the articulated coralline red algae Corrallina officinalis and Arthrocardia corymbosa, (Corallinaceae, Rhodophyta) using a fluorescent brightener - Soutschka, Nadine (Department of Biological Sciences, 2017)
Coralline algae are important components of the coastal marine ecosystem, making it crucial to understand influences on their production and their growth rate in general. A few attempts have been made to quantify coralline growth rate using various methods, however since they have been reported to be slow growers it is difficult to quantify their growth rate accurately. Calcofluor white is an optical brightener that can be used to stain cell walls of plants and has been used to stain articulated corallines in the field, which proved to be a useful and accurate method for measuring coralline growth rate. This study tested the use of Calcofluor white for measuring growth of articulated (geniculate) coralline algae found on the south-west coast of South Africa, and made a series of methodological tests on the use of the stain. The growth rate of Corallina officinalis and Arthrocardia corymbosa were compared by growing them in culture in aerated plastic bags at 15°C and 16 hr light:8hr dark. Only C. officinalis produced measurable growth in culture (0.08-0.09 mm day⁻¹). Further tests were carried out only on C. officina/is. Additionally, an attempt was made to stain C. officinalis in a rock pool, in situ. In culture, the exposure time to the dye was tested for effect on growth rate. Growth rates were similar after 8 days, but after 20 and 28 days thalli stained for 15 min grew significantly slower than those stained for 5 or 30 min. However, this effect seems to be caused by factors other than staining time (e.g. light or water movement in the culture bags). Growth in culture of C. officinalis was strongly effected by salinity: at 60% saltwater (±21 ppt) growth fell to 0.03 mm day⁻¹ , and there was no growth in 30% saltwater (±10 ppt). The effects of 3 preservation methods on staining in C. officinalis were also tested. The stain was unaffected by drying the thalli or preserving them in 5% formalin in seawater. Preservation in 70% alcohol/20% glycerol/IO% freshwater (a common method of preserving coralline for DNA analysis) reduced stain visibility, particularly when thalli had only been stained for 5 min. The study confirms that Calcofluor white is an effective fluorescent dye for staining coralline red algae. Furthermore, staining can be as short as 5 min and thalli can be preserved without affecting the stain, so that thalli can be stained in situ, preserved, and brought to the laboratory for measurement.